2006
DOI: 10.1210/en.2005-0690
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characterization of a Heterodimer-Selective Retinoid X Receptor Modulator: Potential Benefits for the Treatment of Type 2 Diabetes

Abstract: Specific retinoid X receptor (RXR) agonists, such as LG100268 (LG268), and the thiazolidinedione (TZD) PPARgamma agonists, such as rosiglitazone, produce insulin sensitization in rodent models of insulin resistance and type 2 diabetes. In sharp contrast to the TZDs that produce significant increases in body weight gain, RXR agonists reduce body weight gain and food consumption. Unfortunately, RXR agonists also suppress the thyroid hormone axis and generally produce hypertriglyceridemia. Heterodimer-selective R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 38 publications
1
50
0
4
Order By: Relevance
“…AP-1 is a rather ubiquitous inflammatory transcription factor, and it is responsible for the regulation of a large number of genes, including MMP-3, which were unaffected by LG268 treatment. Previous studies characterizing LG268 (41)(42)(43) indicated that treatment with this rexinoid activates a limited number of RXR-containing NHR dimers, including RXR-RXR, RXR-farnesoid X receptor, RXR-liver X receptor, RXR-peroxisome proliferator-activated receptor ␣ [PPAR␣], and RXR-PPAR␥. In reviewing the literature, we found substantial data linking specific ligands for PPAR␥ to inhibition of MMP production and therapeutic activity in models of arthritis (44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…AP-1 is a rather ubiquitous inflammatory transcription factor, and it is responsible for the regulation of a large number of genes, including MMP-3, which were unaffected by LG268 treatment. Previous studies characterizing LG268 (41)(42)(43) indicated that treatment with this rexinoid activates a limited number of RXR-containing NHR dimers, including RXR-RXR, RXR-farnesoid X receptor, RXR-liver X receptor, RXR-peroxisome proliferator-activated receptor ␣ [PPAR␣], and RXR-PPAR␥. In reviewing the literature, we found substantial data linking specific ligands for PPAR␥ to inhibition of MMP production and therapeutic activity in models of arthritis (44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…However, another insulin pathway, namely that involving PKCζ, is also involved in translocation of SLC2A4 [16]; it was inhibited in the presence of TNFα, but was not restored by T0901317. Accordingly, synthetic NR1HR agonists have been reported to improve glucose tolerance in genetic and dietary models of type 2 diabetes [6,8] and to increase glucose-induced insulin secretion by islets [7], very similar effects to those elicited by thiazolidinediones [34] and synthetic activators of RXR [35]. Moreover, NR1HR agonist treatment suppresses hepatic gluconeogenesis [6], inhibits synthesis of proinflammatory cytokines [36] and induces desirable changes in cholesterol metabolism [37], favourable features for a potential drug against diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Along the same line, the poorly active rexinoid HX600 acts as an efficient activator of RXRα-and RXRγ -Nur77/NR4A1 dimers, but not of RXRβ-Nur77 dimers, the latter feature being in line with the reported inability of RXRβ to dimerize with Nurr1/NR4A2 95 . Interestingly, the rexinoid LG101506 activates selectively RXR-PPARγ heterodimers, but not RXR-RAR or RXR-LXR heterodimers 15 . In agreement with the predicted biological consequences of PPARγ activation, this compound lowered significantly blood glucose levels in genetically diabetic mice and did not increase blood triglyceride levels in Sprague-Dawley rats…”
Section: Towards Heterodimer-specific Rexinoidsmentioning
confidence: 98%